Development Of Interactive Multimedia Based Learning Media Using Youtube On Sunnah Prayer Materials In SDIT Al-Izzah Kotabaru South Kalimantan - Ummu Khumairah Husin Lubis; Nurmawati Nurmawati (LPPPIPublishing, 2022)
The purpose of this development research is to find out the development of Interactive Multimedia-Based Learning Media using YouTube in learning the Sunnah Prayer material at SDIT Al-Izzah Kotabaru, South Kalimantan. To find out the results of students' religious learning with the Sunnah Prayer material at SDIT Al-Izzah Kotabaru, the development model used is ADDIE which has 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation (Evaluation). The subjects of this study were students of SDIT Al-Izzah Kotabaru class V. The feasibility of learning media refers to the results of media assessments by experts on the developed learning media. Interactive Multimedia-based religious learning media using YouTube on the Sunnah Prayer material developed has met the appropriate/valid criteria for use for fifth-grade SDIT students. The results of the media assessment by the validator I obtained a score of 95.4 with the